Physico-mechanical properties of heat treated Sesenduk using direct contact thermal method - Abdul Kadir, Nur Shakirin (2019)
The main purpose of this study is to improve the dimensional stability, increase biological durability, enhanced weather resistance and decrease shrinkage and swelling wood. The sample of Sesenduk with 200mm x 70mm x 10mm, 300mm x 70mm x 15mm and 400mm x 70mm x 20mm in a green condition are being treated with different temperature which is 160oC, 190oC and 220oC, also with the different time where 30 minutes, 45 minutes and 60 minutes are being tested on mechanical and physical properties to identify the physical properties changes (surface roughness, colour changes water absorption and thickness swelling). The sample that being tested shows those 45 minutes with 190oC and the thickness of 15mm are the most optimum treatment to produce Sesenduk with the best physico-mechanical properties.